Predictors of Preventive Nutritional Behaviors of Cardiovascular Diseases among Women Referred to Community Health Centers of Shahid Beheshti University of Medical Sciences Based on the Health Belief Model - Sakineh Rakhshanderou; Hossein Hatami; Shahnaz Delbarpoor-Ahmadi (Shahid Beheshti University of Medical Sciences, 2019)
Background and Objective: Some cardiovascular diseases can be prevented by identifying the risk factors such as smoking, unhealthy diet and obesity, physical inactivity, high blood pressure, diabetes, and hyperlipidemia. The present study aimed to determine the predictors of preventive nutritional behaviors of cardiovascular diseases among women referred to community health centers of shahid beheshti university of medical sciences based on the health belief model in 2017. Materials and Methods: In this descriptive-analytical study, 370 women aged 15-49 years referred to health centers of Shahid Beheshti University of Medical Sciences were selected by multistage sampling. The data collection tool was a standard questionnaire based on health belief model constructs. The questionnaires were completed whithin a month and data were entered into SPSS-16 software. Then, data were analyzed by Pearson correlation test and multiple regression analysis. Results: The mean (SD) age of participants was 35.9 (8.1). Decreased mean (SD) of perceived barrier structures 56.6 (13.4) (P<0.001), and increased perceived self-efficacy 81.8 (11.9) (P=0.04) and perceived susceptibility 76.1 (13.3) (P<0.001), improved protective nutritional behaviors of cardiovascular diseases with a mean (SD) score of 70.8 (10.9). Conclusion: The study showed that decreased perceived barriers and increased self-efficacy and perceived susceptibility improved the preventive nutritional behaviors for cardiovascular diseases among women. In addition, perceived barriers were also the most prominant predictor of preventive nutritional behaviors of cardiovascular diseases among women.   DOI: http://doi.org/10.22037/ch.v6i1.21813